Effect of long-term burn-pruning on the flora in a lowbush blueberry ( Vaccinium angustifolium Ait.) stand - Penney, B. G.; McRae, K. B.; Rayment, A. F. (Canadian Journal of Plant Science, 2008)
The effect of burn-pruning on the flora in a natural stand of lowbush b lueberry was studied over a 24-yr period in Newfoundland and Labrador, Canada. Treatments were: not burned and burn-pruned every 2nd, 3rd, or 4th year. A vegetative survey was conducted before burning and periodically in succeeding years. Following statistical analyses, species were grouped according to their response to burning, as follows: those not significantly affected; those eliminated or whose frequency of occurrence was reduced; and those whose occurrence was increased. Initially, burning virtually eliminated Juniperus communis var. depressa, Empetrum nigrum, Cladina rangiferina, Lycopodium clavatum and Pleurozium schreberi, reduced the frequency of occurrence of nine species by 6 to 69%, and increased 13 others by 1 to 2050%. With burning, Polytrichum commune and Fragaria virginiana ssp. glauca, in particular, increased very early in the study to become two of the most prevalent species. Also, except for some initial effects of burning, the lowbush blueberry and some initially prevalent species (Festuca filiformis, Maianthemum canadense, Danthonia spicata, Cornus canadensis and Luzula multiflora var. acadiensis) remained among the most dominant species. Of the species studied, only seven each of those increased or decreased by burning were affected by the burn-pruning cycle. In both groups, the greatest increases or decreases in the frequency of occurrence were obtained with the 2-yr burn-pruning cycle. Key words: Lowbush blueberry, Vaccinium angustifolium, burning, pruning, plant succession, weeds, fire, flora